2,3-Di-4-pyridylbutane-2,3-diol - Niu, Y.Y.; Ng, S.W.; Zain, Sharifuddin Md; Liu, X.C. (International Union of Crystallography, 2005)
The molecule of the title compound, C14H16N 2O2, lies on a centre of inversion located at the mid-point of the central C-C bond. O-H⋯N hydrogen bonds link adjacent molecules into a layer motif. © 2005 International Union of Crystallography Printed in Great Britain - all rights reserved.